Challenges in Healing Wound: Role of Complementary and Alternative Medicine - Monika, Prakash; Chandraprabha, Mathikere Naganna; Rangarajan, Annapoorni; Waiker, P. Veena; Chidambara Murthy, Kotamballi N. (Frontiers in Nutrition, 2022)
Although the word wound sounds like a simple injury to tissue, individual’s health status and other inherent factors may make it very complicated. Hence, wound healing has gained major attention in the healthcare. The biology wound healing is precise and highly programmed, through phases of hemostasis, inflammation, proliferation and remodeling. Current options for wound healing which includes, use of anti-microbial agents, healing promoters along with application of herbal and natural products. However, there is no efficient evidence-based therapy available for specific chronic wounds that can result in definitive clinical outcomes. Under co-morbid conditions, chronic would poses numerous challenges. Attempts have been made to understand the wound at the molecular level, mainly through the analysis of signature genes and the influence of several synthetic and natural molecules on these. We have outlined a review of challenges in chronic wound healing and the role of Complementary and Alternative Medicines (CAMs) in chronic wound management. The main focus is on the applications and limitations of currently available treatment options for a non-healing wound and the best possible alternates to consider. This information generates broader knowledge on challenges in chronic wound healing, which can be further addressed using multidisciplinary approach and combination therapies.